Corporate social responsibility and traditional practices recognised as violence against women in Nigeria's oil region. Issue 4 (19th May 2022) - Uduji, Joseph Ikechukwu; Okolo-Obasi, Elda Nduka; Asongu, Simplice Anutechia
ABSTRACT: We examine the impact of multinational oil companies' (MOCs') corporate social responsibility (CSR) on traditional practices recognised as violence against women and girls (VAWG) in Nigeria's oil region. Results from a combined propensity score matching and logit model indicate that MOCs' CSR plays a significant role in empowering women and girls with information and education to protect their human rights. It is implied that CSR offers an opportunity for MOCs to help address the prevalence of child early and forced marriage, female genital mutilation/cutting, sex trafficking, virginity testing, and taboos through a business case for stakeholders' human rights protection.